# ch4 - 72 Section 4.1 CHAPTER 4 Section 4.1, Page 224 2....

This preview shows pages 1–12. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 72 Section 4.1 CHAPTER 4 Section 4.1, Page 224 2. Writing the equation in standard form of Eq.(2), we obtain y” + [(sint)/t]y" + (3/t)y = cost/t. The functions p1(t) = sint/t, p3(t) = 3/t and g(t) = cost/t each have a discontinuity at t = 0. Hence Theorem 4.1.1 guarantees that a solution exists for t < 0 or for t > 0. 4. The equation is in standard form with pl(t), p2(t) and lnt is II p3(t) being continuous for all t. However, g(t) defined and continuous only for t > 0. 2t—3 2t2+1 3t2+t 8. We have W(fl,f2,f3) = 2 4t 5t+1 = 0 for all t. 0 4 6 Thus by the extension of Theorem 3.3.1 (or by the discussion following Eq.(8), the given functions are linearly dependent. To find a linear relation we have c1(2t—3) + c2(2t2+1) + c3(3t2+t) = (2c2+3c3)t2 + (201+ca)t + (~3cl+c2) which is zero when (2c2+3c3) = 0, 2cl+c3 = 0 and --3cl+c2 = 0. Solving, we find c:1 : 1, c2 = 3 and c3 = —2 and hence (2t—3)+3(2t2+1)—2(3t2+t) = o. 13. That et, e t, and e_2t are solutions can be verified by direct substitution. For y = e'zt, y' = -2e"2t, y" = 4e_2t, and y”’ = -—8e—2t and thus (—8e'2t) + 2(4e_2t) — (—2e_2t) — 2(e“2 that e—2t is a solution. Computing the Wronskian we t) = 0, verifying obtain, at e—t e~2t I 1 l 1 W(et'e—t'e—2t) = at _e_t _Ze_2t = 9-21: 1 _1 “2 = _6el—2t et e—t 49—2t 1 1 4 17. To show that the given Wronskian is zero, it is helpful, in evaluating the Wronskian, to note that (sinztf = Zaintcost = sin2t. The result can also be obtained directly since 1 sinzt = (1 — cos2t)/2 = 13(5) + (—1/2)cosZt and hence 19a. 19b. 19c. 23. 25a. 25b. Section 4.4 73 sinzt is a linear combination of 5 and cosZt. Thus the functions are linearly dependent and their Wronskian is zero. If y 2 t“ then y' = ntn‘l, y" = n(n—1)t“'2, y“‘1 = [n(n—1)(n—2)---21t. so 12“” = [n(n-l)(n—2)“'(2)(1H- The nth derivative of ert is y‘n’ — rnert. If we let L[y} = y(4) — 5y” + 4y and if we use the result of Prob. 19b, we have L[ert] = (r4 — 5r2 + 4)ert. Thus ert will be a solution of the D.E. provided (12—4)(r2—1) = 0. Solving for r, we obtain the four . t —t 2t ~2t . solutions e , e , e and e . Since t — 2t — . W(e , e t, e , e 2t) ¢ 0, the four functions form a fundamental set of solutions. Writing the equation in the form of Eq.(2), we have Zdt _f_:w c p1(t) = —- and from Prob. 20, W — ce = —37. t On 0 < t < 1, f(t) = t3 and g(t) = t3. Hence there are nonzero constants, c1 = 1 and c2 = -1, such that On —1 < t < 0, c1f(t) + czg(t) O for each t in (0,1). 1 defines f(t) —t3 and g(t) t3; constants such that c1f(t) + c2g(t) (-1,0). Thus f and g are linearly dependent on 0 < t < 1 and on -1 < t < 0. thus c1 = c2 0 for each t in We will show that f(t) and g(t) are linearly independent on «1 < t < l by demonstrating that it is impossible to find constants c1 and c2, not both zero, such that c1f(t) + czg(t) O for all t in (-1,1). two such nonzero constants and choose two points t0 and t1 in ~l < t < 1 such that tO < 0 and t1 > 0. Assume that there are Then —cltg + cztg 0 and citi+ czti — 0. These equations have a nontrivial solution for c1 and 02 only if the determinant of coefficients is zero. But the determinant of coefficients is ~2tgti ¢ 0 for t0 and t1 as specified. Hence f(t) and g(t) are linearly independent on —1 < t < l. 74 Section 4 . 2 [ —t3 t3 25c. For -—1 < t < O, W(f,g) = = O and for 0 s t < l, |—3t2 3t2| t3 t3 W(f,g) : = O. This shows that f and g cannot 3t2 3t2 27. be solutions of an equation y” + p(t)y'+ q(t)y = 0 with p and q continuous on -1 < t < l. Differentiating st and substituting in the D.E. we verif}r that y = at is a solution: 2—t et + (2t—3)et — tet + et = 0. ) Now, as in Prob. 26, we let y = v(t)et. Differentiating three times and substituting into the D.E. yields (2—t)etv”’ + (3—t)etv” = O. Dividing by (2—t)et and letting w = v” we obtain the first order separable t—3 1 equation w' = ——w = (—1 + —)w. Separating t and w, t-—2 t-Z integrating, and then solving for w yields w = v" = c1(t—2)e_t. Integrating this twice then gives t _ —t _ t___ t v—clte ~4—c2t+c3 so thaty—ve ~c1t+czte +c3e, which is the complete solution, since it contains the given y1(t) and three constants. Section 4.2, Page 231 2. If -—1 + ix/E = R(cos6+isin9) = Re”, then Rcose = —1 and RsinB = V . Thus R2 = (—1)2 + Mfg)2 = 4 and the angle 6 is given by RcosB = 2cosB = -—l and Rsinﬂ = ZsinB = V . Hence cose = —l/2 and sinB = V3 [2 which has the solution 6 = 2313/3. The angle 3 is only determined up to an additive integer multiple of 3 2n. 8 Writing (lui) in the form Re.l , we have RcosB = l and Raine = —l, which yield R = V2 and 9 = 41/4. Thus (l—i) = V2 sum/4+2”) (where m is any integer) and hence (1_i)1/2 = [21/2el(—ﬂ/4+2m)]1/2 = 21/4el(—J13/8+m2 We obtain the two square roots by setting m = 0,1. They are Elme—iﬂ/Band 21/4ei7n/8. Note that any other integer value of m gives one of these two values. Also note that l—i could be written as l—i = V2 sum/4 + 2m.) 15. 23. 27. 29. Section 4.2 75 It We 100k for solutions of the form y = e Substituting in the D.E., we obtain the characteristic equation 3 r — 3r2 + 3r — l = O which has roots r = 1,1,1. Since the roots are repeated, the general solution is y = clet + cztet + catzet. We look for solutions of the form y = ert Substituting in the D.E. we obtain the characteristic equation 5 in r + 1 = 0. The six roots of —1 = e are obtained by o,1,2,3,4,5 in (4)1”: ei‘“+2m”6. They are = “[37 + i)/2, em” = i, aim/6 = (—ﬁ + i)/2,- = (—ﬁ — i)/2, 63”” eilml6 = (VF; — i)/2. Note that there are three pairs of conjugate roots. The general solution is y = evgt/2[C1COS(t/2) + czsin(t/2)] setting m = eix/é i7n 6 e / = —i, and + e—VEt/2[c3cos(t/2) + c4sin(t/2)] + 05cost + cﬁsint. The characteristic equation is r3 "5r2 + 3r + 1 = 0. Using the procedure suggested following Eq. (12) we try, since a0 = an = 1, r = l as a root and find that indeed it is. Factoring out (r—l) we are then left with rZ—ér—1=O, «I5. The characteristic equation in this case is 12r4 + 31r3 + 75]:2 + 37r + 5 = O. which has the roots 2 1 Using an equation 1 1 solver we find I = —24 —r3, —1 : Zi. Thus ~t/4 st/E it . . y = cle + c2e + e (c3cos2t +c4s1n2t). As in Prob. 23, it is possible to find the first two of these roots without using an equation solver. Factoring then reduces the characteristic equation to a quadratic, which can be solved for the other two roots. The characteristic equation is r3 + r = 0 and hence r = 0, +i, vi are the roots and the general solution is y(t) = c1 + czcost + eBaint. y(0) = 0 implies C1 + c2 = 0, y’(0) = l and y"(0) = 2 Use this last equation in the first to 1 implies c3 = implies —c2 = 2. find :21 = 2 and thus ytt) = continues to oscillate about y = 2 as t —a an 2 — Zoost + sint, which 76 Section 4.2 29- A . n 30' i /\ 30. The general solution is given by Eq. (21). 31. The characteristic equation is r4 — 4r + 4r2 = O, which has the roots r = 0,0,2,2. Thus the general solution would normally be written y(t) = c1 + czt + c3e2t + c4te2t. However, in order to evaluate the c's when the initial conditions are given at t = 1, it is advantageous to rewrite this as y(t) = c1+_c2t + 0592(t—1) + c6(t_l)62(t—1)I which also satisfies the given D.E. 34. 34. The characteristic equation is 4r3 + r + 5 = U, which has 1 roots —1,-§ 2 i, where r1 = —1 can be found as in —t t/2 . Prob.23. Thus y(t) = cle + e (czcost + c3s1nt), y’ﬁt) = —c1e_t + et’2[(c2/2 + c3)cost + ("£22 + c3/2)sint] and n "t t/Z _ y (t) = cle + e [(—3c2/4 + c3)cost + (—cz — 3c3/4)s1nt]. The I.C. then yield c1 + c2 = 2, —c1 + c2/2 + c3 = 1 and c1 — 3c2/4 + c3 = —1. Solving these last three equations give c1 = 2/13, c2 = 24/13 and c3 = 3/13. 37. The approach for solving the D.E. would normally yield Y(t) = Clcost + czsint + cset + cae‘t as the solution. Section 4.3 77 Since cosht = (et+e_t)/2 and sinht = (et—e_t)/2, y(t) can be written as y(t) = clcost + czsint + c3cosht + c4sinht, where c3 and c4 can be written in terms of c5 and as. It is convenient to use cosht and sinht rather than et and e because the I.C. are given at t : 0. Since cosht and sinht and all of their derivatives are either 0 or 1 at t = 0, the algebra in satisfying the I.C. is greatly simplified. _ :ﬁdt 38a.Since pl(t) = O, W = ce = c. 393.As in Sect.3.7, the force that the spring designated by k1 exerts on mass n5 is -3u1. By an analysis similar to that shown in Sect.3.7, the middle spring exerts a force of —2(ul—u2) on mass :111 and a force of —2(u2—u1) on mass n5. Thus Newton's Law gives mlul" = —3ul —2(ul—u2) and m2u2" = ~—2{u2—u1), where u1 and u2 are measured from their equilibrium positions. Setting the masses equal to l and rewriting each equation yields Eqs.(i). In all cases the positive direction is taken in the direction shown in Figure 4.2.4. 39b.The characteristic equation for (ii) is r4 + 7r2 +6 = 0, or (r2+1)(r2+6) = 0. Thus the general solution of Eq,(ii) is u1(t) = clcost + czsint + c3coswl6 t + c4sinx/6 t. 39c.From Eq.(iii) and u1 from 39b we have ul(0) = C1 + c3 = l and u;(0) = 02 + V6504 = O. From Eq.(i) we have u:(0) = 2u2(0) — 5u1(0) = —1 and u1”(0) = 2u;(0} — 5u1(0) = 0, hence —cl - 6c3 = —l and —c2 - 6Vq;c4 we find c1 = 1 and c2 = c3 = c4 = 0, so that u1 = cost. 0. Solving the four equations for the ci The first of Eqs.(i) then gives 2u2 ul" + 5u1 = 4cost and thus u2 = Zoost. Section 4.3I Page 237 1. First solve the homogeneous D.E. The characteristic equation is r3- r2 — r + 1 = O, and the roots are r = —l, t l, 1; hence yE(t) = cle' + czet + catet. Using the 78 Section 4.3 superposition principle, we can write a solution as the sum of particular soluti ns corresponding -t to the D.E. y”—y’-yHy = 2e and y”—y'—Y+y = 3. Our initial choice for a particular solution, Y1, of the particular is a solution of the Thus, first equation is Ae‘t; but e—t homogeneous equation so we multiply by t. Y1(t) = Y2(t) = B, and there is no need to modify this choice. Ate—t. For the second equation we choose The constants are determined by substituting into the individual equations. We obtain A = 1/2, B = 3. Thus, the general solution is y = cle‘t + czet + c3tet + (ts—t)/2 + 3. The characteristic equation is r4 — 4r2 = r2(r2-4) = 0, 21'. so yc(t) = c1 + cat + c3e_2t + c4e . For the particular solution correspnding to t2 we assume Y1 = t2(At2 + Bt + C) and for the particular solution corresponding to et we assume Y2 = Det. Substituting Y1, in the D.E. yields —48A = l, B = 0 and 24A—8C = 0 and substituting Y2 yields ~3D = 1. Solving for A, B, C and D gives the desired solution. The characteristic equation for the related homogeneous D.E. is r3 + 4r = 0 with roots r = 0, +2i, —2i. Hence yc(t) = c1 + czcosZt + c3sin2t. The initial choice for Y(t) is At + B, but since B is a solution of the homogeneous equation we must multiply by t and assume Y(t) = t(At+B). A and s are found by substituting in the D.E., which gives 4 A = 1/8, B = 0, and thus E the general solution is 3' y(t)=c1+c2c052t+c3sin2t+(1/8)t . Applying the I.C. we have 2 no) =o=>c1+c2=0. y'(0) = 0 =9 2C3 = 0, y”(0) = 1 =9 ~4c2 + 1/4 = 1, which have the solution c1 = 3/16, c2 = —3/16, c3 = and * i 4 5 i I D 1 2 0. For t = n, 2n... the graph will be tangent to t2/B and for large t the graph will be approximated by t2/8. 13. 17. 20. 22a. Section 4.3 79 The characteristic equation for the homogeneous D.E. is 3 - 2r2 + r Hence the r = 0 with roots I = 0,1,1. . . t complementary solution is yc(t) = C1 + czet + c3te . We I - I I HF J' 3 conSider the differential equations y — 2y” + y = t and y” - 2y" + y' 2et separately. Our initial choice for a particular solution, Y1, of the first equation is Aot3 + Alt2 + Azt + A3; but since a constant is a solution of the homogeneous equation we must multiply by t. Thus Y1(t) t(Aot3 + A1122 + Azt + A3). t Be , For the second equation t but since both e and tet we first choose Y2(t) = are solutions of the homogeneous equation, we multiply by t2 to obtain Y2(t) = Btzet. Then Y(t) Y1(t) + Y2(t) by the superposition principle and y(t) yh(t) + Y(t). The characteristic equation is 4 3 r(r~l)(r2—l) 0, r — r . . _ —t t t solution is yb(t) m (21 + c2e + cae + c4te . so the complementary The — r2 + r superposition principle allows us to consider separately the D.E. y‘4) — y — y" +y’ t2 + 4 and (4) tsint. For the first equation our Y S _ Y!!! __ y." + Yf initial choice is Y1(t) Act2 + Alt + A2; but this must I" be multiplied by t since a constant is a solution of the Hence Y1(t) t(A0t2 + Alt + A2). the second equation our initial choice that (Bot + Bl)cost + + (Cot + C1)sint does not need to be For homogeneous D.E. Y2 — modified. Hence Y{t} = t{Aot2 + Alt + A2} + (Bot + Bﬂcost + (Cot. + c1)sint. (D—a)(D—b)f = (D—a)(Df—bf) = D2f — (a+b)Df + abf and (D—b)(D—a)f = (D—b)(Df—af) = sz — (b+a)Df + baf. Since a+b = b+a and ab = be, we find the given equation holds for any function f. The D.E. of Prob.13 can be written as D(D—1)2y = t3 + Zet. Since 13“ annihilates t3 and (9—1) annihilates 2st, we have D5(D-1)3y = 0, which corresponds to Eq.(ii} of Prob. 21. The solution of this equation is ﬁt) = Alt4 + Azt3 + A3t2 + A4t + A5 + (131+;2 + 321-. + B3)e_t. Since A5 and (th + :33)!t are solutions of the homogeneous equation related to the original D.E., they 80 22b. If y = te‘t Section 4.4 deleted and thus it" + 113:3 L d t may be t + A3t2 + A4t + B1t2e_ . m .i .- n then Dy = —te_t and Dzy = te—t - 2e‘t, so (D+l)2y = (D2+2D+l)y = 0 and thus (D+l)2 annihilates t te_ . Likewise D2-1 annihilates 2c05t. Thus (D+l)2(DZ+1) annihilates the right side of the D.E. of Prob.l4. + e—t 22e.D3(D2+1)2 annihilates the right side of the D.E.of Prob.l7. Section 4.4, Page 242 1. The complementary solution is ya = c1 + czcost + casint and thus we assume a particular solution of the form Y = u1(t) + u2(t)cost + u3(t)sint. Differentiating and assnming Eq.(5), we obtain Y’ = —uzsint + u3cost and (a). Continuing this process we obtain Y” = J J I . u1 + ugcost + u3Sint = 0 —u2cost - u3sint, and —u;sint + ugcost = 0 (b) a l' r - and Y”' = uzsint — uacost ~ uzcost — ussint. Substituting Y and its derivatives, as given above, into the D.E. we obtain the third equation: (C}« Equations (a), (b) and (c) constitute Eqs.(10) of the text for this problem and may be solved to give Thus I I _ ~u2cost — u3s1nt = tant r t I I . 2 u1 = tant, u2 = —Sint, and u3 = -Sin't/oost. sint — ln(sect + tant) u1 = —lncost, u2 cost and u3 = and substitution into Y above gives Y —1ncost + 1 — (sint)ln(sect + taut), since sinzt + coszt = 1 Note that the constant absorbed in C1 in yC above. 1 can be 1 by sect and use sect, Replace tant in Eq.(c) of Prob. Eqs.(a) and (b) as in Prob.1 to obtain u; = u; = —1 and u; = —sint/cost. Replace sect in Prob. 7 with e_tsint. 11. Section 4.4 81 Since et, cost and sint are solutions of the related homogenous equation we have Y(t) = (10) then are t . ule + uzcost + u3s1nt. Eqs. I t , J . ule + uzcost + u3s1nt = 0 t . ule — ugsint + ugcost = 0 u’let — ugcost — ugsint = sect. Using Abel's identity, W(t) = cexp(:Iﬁl(t)dt) = Get. 1 1 0 Using the above equations, W(O) = 1 0 1 = 2, so 1 —1 0 c = 2 and W(t) = Zet. From Eq.(11), we have 0 cost sint sect W1{t) ua(t) = t , where W1 = 0 —sint cost = l 28 1 —cost -sint and thus . 1 _ . . u1(t) =-§e tloost. LikeWise r sect W2(t) 1 1.12 = —————e4——— = ———sect(cost — sint) and 2et 2 ' sect W3(t) 1 u3 = —————————— = —a-sect(sint + cost). Thus 2et 2 1 eHSds 1 1 1 1 = — ———, u2 = -—t — —1n(cost) and 113 = ——t + —-ln(cost) 2 ocos(s) 2 2 2 2 which, when substituted into the assumed form for Y, yields the desired solution. ' we may use the Since the D.E. is the same as in Prob. 7. 0. complete solution from that, with to = Thus 1 1 17(0) = 01 + '32 = 2; YWO) = C1 + C3 — E + E = —1 and "(0) + 1 1 1 1 = C -' C — - + — = , Y 1 2 2 2 1a A computer algebra system may be used to find the respective derivatives. Note that the solution is valid only for a 0 s t < 3-, where we see ° 02 m u u 1 u 14 1a the vertical asymptote. 82 14. 16. Section 4.4 Since a fundamental set of solutions of the homogeneous D.E. is yl = et, y2 = cost, Y3 = sint, a particular solution is of the form Y(t) = etulg't) + (cost)u2(t) + (sint)u3(t). Differentiating and making the same assumptions that lead to Eqs.(10), we obtain uaet + uécost + ugsint : G urlet - uésint + ugcost = G Git) Solving these equations using either determinants or by (1/2)e‘tg(t). u'2=(1/2)(sint - cost)g(t),u’3 = ——(l/2)(sint + cost)g(t). Integrating these and substituting into Y yields t 1 t —5 Eye]; 9 g(s)ds + cost 0 r t l f . ule - uzcost — u3sint — . . . . 1' elimination, we obtain u1 = t Y(t) = ﬂ [sin(s) — cos(s)]g(s)ds 0 a t I ~sint£1[s1n(s) + cos(s)]g(s)ds}. Putting et, cost and sint inside the respective integrals yields 1: Y(t) = (1/2)]; [et—S + costsin(s) — costc0s(s) - 0 sintsin(s) — sintcos(s)]g(s)ds. If we use the trigonometric identities sin(A—B) = sinAcosB - cosAsinB and cos(A—B) = cosAcosB + sinAsinB, we obtain the desired result. Note: Eqs.(11) and (12) of this section give the same result, but it is not recommended to memorize these equations. The characteristic equation has the repeated roots r = 1,1,1 and thus the particular solution has the form Y = etu1(t) + tetu2(t) + tzetusrt). making the same assumptions as in the earlier problems, Differentiating, and solving the three linear equations for u}, u;, and u; yields ’ 2 -t f at I _t u1 =(1/2)t e g(t), u2 = —te g(t) and u3 = (l/2)e g(t). Integrating and substituting into Y yields the desired solution. For instance t 1 t tetu2 = —teiﬂ se‘sg(s)ds = —E-t 2tse‘tﬁ)g(s)ds, and 0 D Section 4.4 83 t—Zet then 9(3) = es/sz, likewise for ud and u . If (t) J. 3 g . . t. (t- and the integration with repect and thus e 5)g(s) = ‘3 s to s is accomplished using the power rule. Note that terms involving t0 become part of the complimentary solution. ...
View Full Document

## ch4 - 72 Section 4.1 CHAPTER 4 Section 4.1, Page 224 2....

This preview shows document pages 1 - 12. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online